UJI KUALITAS MADU PADA BEBERAPA WILAYAH BUDIDAYA LEBAH MADU DI KABUPATEN PATI - Iffa Illiyya Fatma; Sri Haryanti; Sri Widodo Agung Suedy (Jurnal Akademika Biologi, 2017)
Honey is the natural sweet substance produced by honey bees from the nectar of flowers. Honey composition is very complex, it contains at least 181-200 different substances, hence the enormous benefits of honey within pharmaceutical industry, food, beverage, and aesthetics. Although the demand for honey in Indonesia has been increasing, there is still no honey quality certification labeled on its product. This study used honey from several beekeeping region in Pati regency which has not been certified. The research aims to analyze honey quality based on water content, acidity, and total sugar. The sampling was purposive sampling method in the three different districts in Pati Regency, those were Gembong District, Gunungwungkal District, and Tlogowungu District, because in general this area is the main honey producer as there are many beekeepers and there is still no honey quality information labeled on it. This research used a Completely Randomized Design (CRD) with 3 treatments (locations) 4 replications from different beekeeper in each region. The water content and total sugar used a refractometer and acidity used titration. The research found that there is a significant difference between honey quality from different beekeeping region. The water content is ranged from 24-27,8%, acidity 59,2-68,3ml NaOH/kg, and total sugar 70,6-74,5 oBx. The highest honey quality is obtained from Gembong District with water content 24%, acidity 59,2ml NaOH/kg, and total sugar 74,5oBx.Keywords: Apis mellifera, water content, acidity, total sugar.